Perlindungan Konsumen Terhadap Transaksi Jual-Beli Voucher Game Online Menurut Undang-Undang nomor 8 Tahun 1999 Tentang Perlindungan Konsumen dan Undang-Undang Nomor 11 Tahun 2008 Tentang Transaksi Elektronik - Jason Samuel; R.M. Gatot P. Soemartono (Jurnal Hukum Adigama, 2022)
Pandemic Covid-19 has made online game enthusiasts increase rapidly, so there is a great opportunity for businesses to buy and sell online game vouchers in Indonesia. Coupled with the government organizing official matches such as the E-Sports President's Cup which makes online game enthusiasts increase. The rapid development of technology has also made some parties take advantage of these technological advances for personal gain. In the process of buying and selling online game vouchers, there are several cases that are the subject of this scientific writing research. For this reason, it is necessary to study the violation of buying and selling online game vouchers that occurs from the perspective of the ITE Law and UUPK, as well as legal actions to regain the rights owned by consumers. The conclusion obtained is that consumers can make criminal complaints to the local resort police or consumers can make a report to BPSK or LPKSM. If you make a criminal complaint to the local resort police, it can be continued as a criminal offense, and if it is through BPSK or LPKSM, it can be resolved through arbitration or mediation.